Loop interference suppression based on space projection in full-duplex MIMO relays - Ji-song YANG; Hao LIU; Chen SUN (Tongxin xuebao)
The system model including base station,full duplex MIMO relay and user station was established,and then obtained the loop interference matrix.While the case that loop interference signal's maximum multipath delay was greater than the symbol period was taken into account,signal space projection filters were designed to suppress the loop interference according to the space expanded by loop feedback interference matrix.Confronted the loop interference ma-trix full rank or not,filter design was based on subspace projection or null space projection algorithm.It was discussed that the projection algorithm how to influence the residual interference signal and the bit error rate of the relay station.Theoretical analysis and simulation results prove that the proposed space projection algorithm has ideal effect on sup-pressing loop interference.